IMPLEMENTASI KHIYAR SYARAT PADA GARANSI BEBAS PENGEMBALIAN E-COMMERCE SHOPEE - Asmarini, Andini; Nurinayah (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2025)
The Free Return Guarantee offered by e-commerce Shopee gives consumers the right to return the product if they change their mind about purchasing a product without a prior checking process by the seller. In sharia economic law, principles such as honesty and transparency are highly emphasized. This study aims to examine the implementation of the Free Return Guarantee in Shopee e-commerce transactions and assess its conformity with the concept of khiyār syarṭ under sharia economic law, in order to determine whether this policy fulfills the expected principles of sharia economic law in commercial transactions. This article is descriptive research. In extracting and collecting data, the method used is library research, to be able to study library materials and documents which are the main source of information. The research results show that so far, the Free Return Guarantee program implemented by e-commerce platforms such as Shopee can be considered in accordance with the principles of Sharia Economic Law, as long as the policy is designed taking into account the rights and the obligations of both parties (consumers and sellers). Moreover, this policy aligns with the concept of khiyār syarṭ in Islam, which allows a conditional option period in transactions to ensure fairness and mutual consent.